Do PT and APTT sensitivities to factors' deficiencies calculated by the H47‐A2 2008 CLSI guideline reflect the deficiencies found in plasmas from patients?. (4th September 2015) - Martinuzzo, M.; Barrera, L.; Rodriguez, M.; D'Adamo, M. A.; López, M. S.; Otaso, J. C.
Summary: Introduction: Prothrombin time (PT) and activated partial thromboplastin time (APTT) sensitivity for detecting isolated factor deficiencies varies with different reagents and coagulometers. The Clinical and Laboratory Standards Institute (CLSI) H47A2 guideline proposed a method to calculate these sensitivities, but some inconsistency has been reported. This study aimed to calculate factor sensitivities using CLSI guideline and to compare them with those obtained from single factor‐deficient patients' data. Methods: Different mixtures of normal pooled and deficient plasmas were prepared (<1IU/dL to 100 IU/dL) according to the CLSI H47A2 guideline. PT with rabbit brain (RB) and human recombinant (HR) thromboplastins, APTT and factors' activities were measured in an ACL TOP coagulometer. Sensitivities (maximum factor concentration that produces PT or APTT values out of the reference range) were calculated from mixtures and from patients with single‐factor deficiencies: 17 factor FV, 36 FVII, 19 FX, 39 FVIII, 15 FIX 15 FXI and 24 FXII. Results: PT sensitivity with RB was as follows: FV 38 and 59, FVII 35 and 58, FX 56 and 64 IU/dL; PT sensitivity with HR was as follows: FV 39 and 45, FVII 51 and 50, FX 33 and 61 IU/dL; and APTT sensitivity was as follows: FV 39 and 45, FX 32 and 38, FVIII 47 and 60, FIX 35 and 44, FXI 33 and 43, FXII 37 and 46 IU/dL, respectively. Conclusions: Reagent–coagulometer combination has adequate sensitivities to factor deficiencies according to guideline recommendations (>30 IU/dL). These should not be considered as actual sensitivities because those obtained by analysing patients' plasmas with single‐factor deficiencies were higher for most factors and could induce misinterpretation of the basic coagulation test results.